(untitled) (Raparin Journal of Humanities (RJH), 2026)
The concept of quality and its application in digital media play a pivotal role in enhancing performance and improving user satisfaction. Accordingly, this study seeks to identify and assess the extent to which journalistic quality standards are prioritized in digital media and to examine their impact on professional journalistic performance. In the current media landscape, earning public trust has become essential, requiring adherence to recognized standards and mechanisms that ensure the quality of journalistic output. The significance of this research lies in its focus on Kurdish digital media, where evaluating the degree of attention to quality journalism provides valuable insights into how media outlets can align with professional standards, improve their performance, and strengthen public trust. The study aims to investigate the presence and application of journalistic quality standards in media content by analyzing both the quantitative and qualitative aspects of news reporting. The findings indicate that while the Ava News and Ava Media websites demonstrate some adherence to reliability standards, particularly in ensuring message clarity, their practice of impartiality is limited. The analysis reveals a tendency to prioritize governmental perspectives over balanced reporting and a lack of respect for diverse public opinions. Furthermore, the credibility of the news is undermined by the insufficient attribution of authentic sources.